Ontology-based application integration - Paulheim, Heiko (Springer, 2011)
Ontology-based Application Integration introduces UI-level (User Interface Level) application integration and discusses current problems which can be remedied by using ontologies. It shows a novel approach for applying ontologies in system integration. While ontologies have been used for integration of IT systems on the database and on the business logic layer, integration on the user interface layer is a novel field of research. This book also discusses how end users, not only developers, can benefit from semantic technologies. Ontology-based Application Integration presents the development of a software framework including a detailed ontology about user interfaces and interactions. This includes a running case study of a real world integrated emergency management system. The last section of this book discusses useful features that can be built on top of the framework for improving the user experience with future integrated information systems. Ontology-based Application Integration is designed as a reference book for practitioners and researchers who understand and work with the principles of applying semantic web technologies to a software engineering problem. This book will also make an excellent reference or secondary text book for advanced-level students concentrating on computer science.